Development and validation of the healthcare provider and family bidirectional digital communication scale - Yu-Chun Diao; Meei-Fang Lou (PLoS ONE, 2025)
Introduction Effective communication between healthcare providers and families is critical in ICUs, yet existing assessment scales predominantly focus on unidirectional, face-to-face interactions. The COVID-19 pandemic accelerated adoption of digital communication modalities that have persisted in contemporary practice. This study developed and validated the Healthcare Provider and Family Bidirectional Digital Communication Scale (HF-BDCS) to address these gaps. Materials and Methods The HF-BDCS was developed through literature review and qualitative interviews with 15 stakeholders (healthcare providers and family members). Content validity was assessed by 5 experts. Psychometric evaluation with 300 participants (100 physicians, 100 nurses, 100 family members) included exploratory factor analysis and internal consistency assessment using Cronbach’s alpha. Results Expert review yielded 14 items with excellent content validity (S-CVI/Ave: relevance=1.00, importance=1.00, clarity=0.98). Exploratory factor analysis produced a 13-item scale with three factors explaining 64.53% of variance: Digital Communication Efficiency and Quality (6 items, 25.87%), Digital Communication Perceptions (5 items, 25.12%), and Digital Communication Regulations (2 items, 13.54%). Internal consistency was good (Cronbach’s alpha=0.80-0.86) across all factors and participant subgroups. Discussion The HF-BDCS is the first validated bidirectional instrument for assessing digital communication in ICUs, demonstrating strong psychometric properties. By capturing both healthcare provider and family perspectives, the scale enables identification of perception discrepancies and supports improvements in digital communication practices, ultimately enhancing patient- and family-centered care in contemporary ICUs.